Pre-Reformation and Reformation Influences on the Development of European Literary Languages - Lewaszkiewicz, Tadeusz (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2023)
The pre-Reformation and Reformation social and religious movements contributed to the development of biblical and religious as well as journalistic and polemical writings, which had a significantly positive impact on the increase in functional efficiency and standardisation of European languages. Translations of The Bible played a special role in the development of European languages as texts with the highest linguistic prestige. Not only did Luther’s Bible (1522–1534) contribute to the unification of German literary language, but its 16th-century translations had an outstanding influence on the development of Dutch and the Scandinavian languages, i.e. Danish, Swedish and Icelandic. The language of Protestant translations of The Bible was regarded in the 16th–17th centuries in France and England as a model of stylistic excellence. Prior to the 16th century, there were fairly rich Celtic writings (Irish, Scottish, Welsh and Cornish), but they were undoubtedly greatly enriched between the second half of the 16th century and the first quarter of the 19th century by Protestant translations of The Bible and other religious texts. The translation work by the Czech brothers (ideological supporters of the Reformation) – Blahoslav’s New Testament (1564) and the Kralice Bible (1579–1593) – is a symbol of the linguistic prowess of the 16th-century Czech language as well as the basis for its rebirth in the 19th century. The linguistic consciousness of the Slovaks was long influenced by the Kralice Bible. Hungarian and Polish Reformation translations of The Bible enriched the history of these languages considerably. A number of European languages owe their actual literary beginnings to the Reformation: Finnish and Estonian (Finnish languages), Latvian and Lithuanian (Baltic languages), Upper Lusatian, Lower Lusatian and Slovene (Slavonic languages). In Croatia, prints financed by Reformation supporters appeared in the 16th century. The Serbian Orthodox New Testament (1847) by Karadžić and The Old Testament (1868) by Daničić were published by the Protestant publishing house of the British Bible Society in London, which also published a translation of the Bulgarian Catholic Slaveykov Bible (1871).